Impact of oral precancerous lesions on oral cancer development in patients with oral lichen planus: a retrospective cohort study of 318 oral lichen planus patients - Chu, Yu-Cheng; Lin, Pei-Yu; Huang, Wan-Ting; Huang, Hsun-Yu; Chen, Chien-Chin (Frontiers in Oral Health, 2025)
BackgroundOral lichen planus (OLP) has been implicated as a potential risk factor for oral cancer. This study aimed to investigate the long-term determinants of oral cancer development following a diagnosis of OLP.Materials and methodsA retrospective cohort study of 318 patients with histopathologically confirmed OLP was conducted at a tertiary medical center from 1995 to 2018. Patients were categorized into two groups based on the presence or absence of oral precancerous lesions (OPLs). Baseline characteristics, underlying medical conditions, and lifestyle factors were compared between groups. The hazard ratio (HR) and the 10-year cumulative risk for oral cancer development were estimated using logistic regression and Kaplan–Meier analysis, respectively.ResultsIn our cohort, a total of 33 patients (10.38%) were diagnosed with oral cancer. After adjusting for confounders, OPLs (HR, 2.98), age over 50 years (HR, 4.36), chronic kidney disease (HR, 4.46), and alcohol consumption (HR, 4.23) emerged as independent risk factors for oral cancer development in patients with OLP (P < 0.05).ConclusionThe current study indicates that the presence of OPLs, including histologically confirmed verrucous hyperplasia and varying degrees of oral dysplasia, is associated with an increased risk of oral cancer development in patients with OLP. Further research is needed to elucidate the underlying molecular mechanisms linking OLP, OPL, and oral cancer occurrence.